Antecedents and Consequences of University Brand Identification - Bhadel, Roshan; Tamang, Govinda (Journal of Business and Social Sciences, 2021)
This research aims to examine the impact of university brand personality, university brand knowledge and university brand prestige on university identification. The study also aims to examine the impact of university identification on advocacy intentions, suggestions for improvements, university affiliation and participation in future activities. In order to execute the study, descriptive research design has been implemented. The study is based on primary data collected through structured questionnaire. A total of 285 respondents have been taken for this study. The findings of the study revealed that all three antecedents; university brand personality, university brand knowledge and university brand prestige has significant positive impact on university identification. Among three antecedents, university brand knowledge has the greatest impact on university identification. Similarly, the findings also revealed that there is significant positive impact of university identification on advocacy intentions, suggestions for improvements, university affiliation and participation in future activities. Likewise, the greatest consequence of university identification is advocacy intentions.